1998
DOI: 10.4039/ent130837-6
|View full text |Cite
|
Sign up to set email alerts
|

SAMPLING PLANT BUGS, LYGUS SPP. (HETEROPTERA: MIRIDAE), IN CANOLA TO MAKE CONTROL DECISIONS

Abstract: The Canadian Entomologist 130: 825 -836 (1998) Plant bugs in the genus Lygus infest canola (Brassica napus L. and Brassica rapa L.) when the crop is producing buds, flowers, and pods. Field studies in cages and open plots show that plant bugs can reduce yield by 20% or more, but have little effect on seed size. A single application of a foliar insecticide when the crop has finished flowering and is beginning to produce pods will prevent most or all of the yield loss. The yield loss of canola that can be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Plant bug counts per square metre were converted to number per 10 sweeps to allow comparison with field plot data, based on studies of the sampling efficiency of sweep netting in canola (conversion factor of 0.526, Wise and Lamb 1998). In the cages where 10 plant bugs were introduced, densities at the end of the season were equivalent to about 78 per 10 sweeps, close to the highest density observed in the field (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant bug counts per square metre were converted to number per 10 sweeps to allow comparison with field plot data, based on studies of the sampling efficiency of sweep netting in canola (conversion factor of 0.526, Wise and Lamb 1998). In the cages where 10 plant bugs were introduced, densities at the end of the season were equivalent to about 78 per 10 sweeps, close to the highest density observed in the field (see below).…”
Section: Resultsmentioning
confidence: 99%
“…This timing was also recommended by Butts and Lamb (1991b) for canola in Alberta. An efficient method for sweep sampling plant bugs in canola and a sequential sampling scheme are described separately (Wise and Lamb 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, speed of net motion has an impact on catch size, with a greater speed collecting more insects (Balogh & Loska 1956), and experienced samplers may capture more insects because they sweep more vigorously and more deeply into the crop (Wise & Lamb 1998). Vegetation density and crop phenology are also significant (Byerley et al 1978, Wilson & Gutierrez 1980, Ellington et al 1984.…”
Section: Sweep-net Capturementioning
confidence: 99%
“…Wise and Lamb (1998) found that there was stability and repeatability in the relationship between variance and mean, allowing sweep nets to be used to detect whether pest populations were above or below level of control. However, there can be biases, for example towards adults and large nymphs of Lygus species (probably due to their location in the upper parts of the plant) (Wise & Lamb 1998). Linders (1995) found the sweep net to be effective for sampling the weevil Trichosirocalus troglodytes on Plantago lanceolata spikes, but the catches were influenced by diurnal and seasonal activity.…”
Section: Chaptermentioning
confidence: 99%
“…Studds and Marra () modified sweep nets to sample higher above ground, but were still limited to a height of ~ 5 m, below that of most forest canopies. In addition, potential human sampling effects (speed, strength, and experience; Wise and Lamb , Cooper et al. ) and weather conditions (Ozanne ) can introduce bias in sweep‐net samples.…”
mentioning
confidence: 99%